Teacher Creativity Skills in Overcoming Limitations of Learning Infrastructure at Alkhairaat Labuha Middle School - Susan N.H. Jacobus; Harol Lumapow; Jumrah Jamil (MultiTech Publisher, 2023)
This research aims to examine and analyze Teacher Creativity Skills in Overcoming Limited Learning Facilities at Alkhairaat Labuha Middle School. The method for writing this article is library research techniques. Reference sources in this writing are taken from published books and scientific articles. The benefit of this writing is to find out Teacher Creativity Skills in Overcoming Limited Learning Facilities at Alkhairaat Labuha Middle School. The results of the research revealed: 1) The facilities and infrastructure for skills lessons are inadequate, 2) the condition of the infrastructure for skills lessons is less supportive because the equipment is old, 3) Teachers have a creative attitude shown by the ability to see problems, look for ideas and ideas in skills lessons.